Notice to submit Quotation for carryout the works under variations or extra works - Please see E BRACU new campus important docuements BoQ other items - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the notice to submit quotation for carryout the works under variations or extra works -please see E BRACU new campus important docuements BoQ other items of BRAC University new campus project.